SIGNALIZED INTERSECTION PERFORMANCE ANALYSIS OF ROUNDABOUT CIGASONG- MAJALENGKA - Abiel Egan; Andri Irfan Rifa'i (LEADER: Civil Engineering and Architecture Journal, 2024)
The signalized intersection at the Cigasong roundabout in Majalengka City is where the Majalengka-Cikijing road, Majalengka-Rajagaluh road, Sindangkasih troops road and Majalengka-Jatiwangi road meet. The traffic problem that often occurs at the Cigasong roundabout is traffic jams, especially at every rush hour the traffic flow increases more densely than at other times. In various regions in Indonesia, traffic lights can also have a negative impact on traffic activities that occur. in urban areas. The aim of this research is to find out how the signalized intersection at the Cigasong roundabout performs, so that traffic problems caused by the many factors above can be resolved. By conducting research on the signalized intersection located at the Cigasong roundabout in Majalengka City, we can gather a number of information about the signalized intersection that coincides with this roundabout, which means that if there is a roundabout there should not be a signalized intersection. Basically, the function of a roundabout is to slow down the speed of vehicles, in contrast to signalized intersections where the average vehicle speed is very fast when the light is green. The Cigasong roundabout is classified as a fairly large roundabout because this roundabout is also a roundabout which connects several road routes to various areas in Majalengka to several sub-districts such as Cigasong, Jatiwangi, Maja and Rajagaluh, as well as directions to other cities such as Cirebon, Indramayu, Kuningan. With this, there will be a suggestion that will be the answer to the problem of signalized intersections located at the Cigasong Roundabout, Majalengka City, so that it can be resolved through research, the results of which are in accordance with what is happening at the roundabout and so that this suggestion can be realized at the Cigasong Roundabout, Majalengka City.